# Calculus

posted by .

Test for convergence or divergence. Indicate the test that was used and justify your answer.

Sigma (lower index n = 4; upper index infinity) 1/(3n^2-2n-15)

• Calculus -

3n^2-2n-15 > n^2 for n>=4,

the series converges since 1/n^2 converges

## Similar Questions

1. ### calculus

test the series for convergence or divergence the series from n=0 to infinity of sin (2^-x) I wasn't sure what test to use to see if this was or wasn't convergent
2. ### Calculus

Determine the convergence or divergence of the series. Find the limit. Indicate the test that was used and justify your answer by showing evidence why the test succeeds or fails. Sigma (lower index n = 1; upper index infinity) 12/[n(n+3)]
3. ### Calculus

Determine the following about the series. Indicate the test that was used and justify your answer. Sigma (lower index n = 1; upper index infinity) [sin((2n-1)pi/2)]/n A. The series diverges B. The series converges conditionally. C. …
4. ### Calculus

Use the Direct Comparison Test to determine the convergence or divergence of the series. Justify your answer and show all of your work. Sigma (lower index n = 1; upper index infinity) 4^n/(3^n-1)
5. ### Calculus

Test for convergence or divergence. Indicate the test that was used and justify your answer. Sigma (lower index n = 2; upper index infinity) [ln(n)]/n
6. ### Calculus

Determine the convergence or divergence of the series. Indicate the test that was used and justify your answer. Sigma (lower index n = 1; upper index infinity) [(-1)^n*3^n]/(n*2^n)
7. ### Calculus

Find the values of x for which the series converges. Sigma (lower index n = 0; upper index infinity) [(x+1)/4]^n
8. ### Calculus

Identify the two series that are the same. a. Sigma (lower n = 4; upper infinity) n(3/4)^n b. Sigma (lower n = 0; upper infinity) (n+1)(3/4)^n c. Sigma (lower n = 1; upper infinity) n(3/4)^(n-1)
9. ### Calculus

Determine convergence or divergence for the following series. State the tests used and justify your answers. Sum (infinity, n=1) 1/(1+e^-n) Sum (infinity, n=1) (2*4*6...2n)/n! Sum (infinity, n=0) (n-6)/n Sum (infinity, n=0) (n-6)/n! …
10. ### c# programming

Trying to create a program using following algorithms. JumpSearch(list,lower,upper,jump,x) {Look for X in List[lower ... upper]. Report its position if found, else report 0. List is sorted in increasing order. upper>=lower>0; …

More Similar Questions